Characterization of Breakage and Washability of ROM Coal using X-ray Computed Tomography. Issue 3 (3rd April 2019) - Lin, C. L.; Miller, J. D.; Nguyen, T.; Nguyen, A.
ABSTRACT: The most critical parameters for the efficient design of coal processing operations depend on the assessment of coal breakage and washability characteristics of the coal resource. X-ray computed tomography (XCT) technology has been demonstrated to have the capability of analyzing washability and fragmentation parameters (particle size, energy, coal type). In this regard, progeny size distributions are obtained from sequential modified drop shatter tests (different input energy levels) and from XCT analysis. In this way, the breakage characteristics (selection and breakage functions) of coal particles are established and the prediction of particle size distribution (PSD) for different levels of energy input is demonstrated.